The N‐terminal pro‐domain of the kalata B1 cyclotide precursor is intrinsically unstructured. Issue 6 (November 2016) - Daly, Norelle L.; Gunasekera, Sunithi; Clark, Richard J.; Lin, Feng; Wade, John D.; Anderson, Marilyn A.; Craik, David J.
Abstract: Cyclotides are plant‐derived, gene‐encoded, circular peptides with a range of host‐defense functions, including insecticidal activity. They also have potential as pharmaceutical scaffolds and understanding their biosynthesis is important to facilitate their large‐scale production. Insights into the biosynthesis of cyclotides are emerging but there are still open questions, particularly regarding the influence of the structure of the precursor proteins on processing/biosynthetic pathways. The precursor protein of kalata B1, encoded by the plant Oldenlandia affinis, contains N‐ and C‐terminal propeptides that flank the mature cyclotide domain. The C‐terminal region (ctr) is important for the cyclization process, whereas the N‐terminal repeat (ntr) has been implicated in vacuolar targeting. In this study we examined the structure and folding of various truncated constructs of the ntr coupled to the mature domain of kalata B1. Despite the ntr having a well‐defined helical structure in isolation, once coupled to the natively folded mature domain there is no evidence of an ordered structure. Surprisingly, the ntr appears to be highly disordered and induces self‐association of the precursor. This self‐association might be associated with the role of the ntr as a vacuolar‐targeting signal, as previously shown for unrelated storage proteins. Abstract : Schematic illustration of kalata B1 precursor protein showing the structured nature of the cystine knot mature domain and the unstructured N‐terminal domain that was systematically truncated in the current study.